Patients with Risk Factors for Complications Do Not Require Longer Antimicrobial Therapy for Complicated Intra-Abdominal Infection. Issue 9 (September 2016) - Rattan, Rishi; Allen, Casey J.; Sawyer, Robert G.; Mazuski, John; Duane, Therese M.; Askari, Reza; Banton, Kaysie L.; Claridge, Jeffrey A.; Coimbra, Raul; Cuschieri, Joseph; Dellinger, E. Patchen; Evans, Heather L.; et al.
A prospective, multicenter, randomized controlled trial found that four days of antibiotics for source-controlled complicated intra-abdominal infection resulted in similar outcomes when compared with a longer duration. We hypothesized that patients with specific risk factors for complications also had similar outcomes. Short-course patients with obesity, diabetes, or Acute Physiology and Chronic Health Evaluation II ≥15 from the STOP-IT trial were compared with longer duration patients. Outcomes included incidence of and days to infectious complications, mortality, and length of stay. Obese and diabetic patients had similar incidences of and days to surgical site infection, recurrent intra-abdominal infection, extra-abdominal infection, and Clostridium difficile infection. Short- and long-course patients had similar incidences of complications among patients with Acute Physiology and Chronic Health Evaluation II ≥15. However, there were fewer days to the diagnosis of surgical site infection (9.5 ± 3.4 vs 21.6 ± 6.2, P = 0.010) and extra-abdominal infection (12.4 ± 6.9 vs 21.8 ± 6.1, P = 0.029) in the short-course group. Mortality and length of stay was similar for all groups. A short course of antibiotics in complicated intraabdominal infection with source control seems to have similar outcomes to a longer course in patients with diabetes, obesity, or increased severity of illness.